PERENCANAAN PERAWATAN POMPA HIDROLIK PADA FORKLIFT 5 TON TIPE FD 50-7 - Wahyudi, Andi; Jannifar, A; Azwinur, Azwinur (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2022)
Damage to the forklift will cause problems that have an impact on inhibiting other activities. So that good and continuous maintenance is needed to maintain the performance of the tool. The purpose of this study is to plan periodic maintenance on the forklift to avoid damage that can stop the operation of the forklift. The method used in this study is to collect data, make direct observations of the damage that occurs to the hydraulic pump, and conduct interviews with experienced mechanics who handle the forklift. The results of the research are maintenance planning with Preventive Maintenance and Corrective Maintenance methods, by implementing daily, weekly, monthly and yearly maintenance activities. In daily maintenance, inspections will be carried out, check all lubrication and perform service. Daily maintenance is carried out every 8 working hours, weekly is carried out every 60 working hours. Monthly maintenance is carried out every 250 working hours, while annual maintenance is carried out every 2500 working hours. The operation of the 5 tons FD 50-7 Forklift unit must be in accordance with the Manual Book. So that the service life of the unit and its components is in accordance with the life time